Um modelo experimental para estudar metáfora: efeitos da punição sobre a frequência de emissão de extensão metafórica do tato - Carvalho, Filipe Cesar da Hora (2020)
Metaphor, as traditional literature knows, represents aspects of verbal behavior studied under the label metaphorical extension of tact. It is a sort of tact generalization, in which the properties of a new stimulus that control verbal response, though present at reinforcement, are not regarded by verbal community as criteria to reinforce this kind of response. In the Verbal Behavior, B. F. Skinner stated that the properties of things or events related with metaphorical extension are matters to experimental research, but in current literature was not possible to find metaphorical extension approached into experimental studies. One of the problems faced in experimental research about metaphorical extension is the lack of method to manipulate variables related to this phenomenon. Therefore this study aimed to develop an experimental procedure to investigate the metaphor phenomenon. For this purpose, two experiments were carried out. Experiment 1 aimed to verify the punishment effect on the metaphorical extension frequency. The procedure was divided into the three following experimental phases: Tact Training phase, in which the participants learned to respond to four different stimulus classes (samples) by selecting a non-sense word (matching stimulus). The selection, in this way, acquired the tact function. On the Punishment of tact “Fite” phase, one of the tacts started to be punished and it was verified whether tacts for the other categories started to be emitted based on adventitious properties of the stimuli. The last phase, Test, did not have programed consequences to all responses. Results of the Experiment 1 showed that the experimental procedure was successful in studying variables involved in the production of metaphors and that the frequency of metaphorical extension increases when faced to some condition of punishment of tact. Experiment 2 was an extension of Experiment 1 and aimed to verify, by turn, punishment effects on the frequency of the metaphorical extension into reversal design. Experiment 2’s procedure was similar to the Experiment 1’s one, having an addition of two experimental phases. Thus, the Experiment 2’s procedure was carried out in this way: Tact Training, Punishment of tact “Fite”, Punishment of tact “Dag”, Fite Test and Dag Test. Experiment 1’s results were replied by the Experiment 2. Therefore experimental method was successful in studying metaphorical extension and enables future studies to verify other properties of the stimuli that underlie to the metaphor.